Kajian Hukum Islam dan UU No. 3 Tahun 2020 terhadap Penambangan Batu di Desa Kasengan, Sumenep - Fiqriyah, Niswatul; Al Fatih, Sholahuddin; Cahyani, Tinuk Dwi (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2025)
This article aims to analyze stone mining which has positive and negative impacts on the community. In Kasengan village, stone mining is managed by individuals or legal entities who own the land. The people can fully utilize this but still maintain it well or manage it as well as possible. Therefore, the author is interested in researching the concept of mining management and analyzing it from the perspective of Islamic law and mining law. This research is empirical research with a statutory and Islamic law approach. Data and information collection was obtained by interviews, observation, and documentation. Apart from that, there are also supporting references available in the library, such as: books, magazines, articles, or other manuscripts related to the research title. Meanwhile, the nature of the research is descriptive analysis. The results of the research reveal that the mining practices in Kasengan Village, Manding District, Sumenep Regency are not permitted according to Islamic law because they cause harm to the survival of local communities, such as floods, landslides and so on due to ex-mining. Meanwhile, according to the law, it is permissible if you obtain a mining business permit and take steps to prevent natural disasters from occurring.